Countering AI-powered disinformation through national regulation: learning from the case of Ukraine - Marushchak, Anatolii; Petrov, Stanislav; Khoperiya, Anayit (Frontiers in Artificial Intelligence, 2025)
Advances in the use of AI have led to the emergence of a greater variety of forms disinformation can take and channels for its proliferation. In this context, the future of legal mechanisms to address AI-powered disinformation remains to be determined. Additional complexity for legislators working in the field arises from the need to harmonize national legal frameworks of democratic states with the need for regulation of potentially dangerous digital content. In this paper, we review and analyze some of the recent discussions concerning the use of legal regulation in addressing AI-powered disinformation and present the national case of Ukraine as an example of developments in the field. We develop the discussion through an analysis of the existing counter-disinformation ecosystems, the EU and US legislation, and the emerging regulations of AI systems. We show how the Ukrainian Law on Counter Disinformation, developed as an emergency response to internationally recognized Russian military aggression and hybrid warfare tactics, underscores the crucial need to align even emergency measures with international law and principles of free speech. Exemplifying the Ukrainian case, we argue that the effective actions necessary for countering AI-powered disinformation are prevention, detection, and implementation of a set of response actions. The latter are identified and listed in this review. The paper argues that there is still a need for scaling legal mechanisms that might enhance top-level challenges in countering AI-powered disinformation.